Probing the Mycobacterial Cell Envelope: CRISPR interference-mediated investigation of two essential genes in the galactan biosynthetic pathway - Conradie, Jesse Robin (Department of Pathology, 2025)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), is a global epidemic and one of the leading causes of death from an infectious organism. TB is treatable, however extended durations of treatment and the rise of multidrug resistant forms of TB contribute towards a health crisis that continues to hinder the global efforts in eradicating this disease. Shortening treatment regimens is a key objective in advancing TB therapy, with the aim of reducing the potential for antibiotic resistance. This highlights the need for the identification of essential cellular pathways in mycobacteria that can be targeted for novel drug development. A key feature of Mtb that confers intrinsic tolerance to many antibiotics is its complex cell envelope. The mycobacterial cell envelope is a dynamic compartment which serves as the interface between the pathogen and its host. It supports vital physiological processes and plays a key role in maintaining intracellular homeostasis. A unique and highly conserved structural component of the mycobacterial cell envelope is the heteropolysaccharide, arabinogalactan. This molecule is comprised of the galactan and Arabinan units, forming the characteristic cell wall core of mycobacterial species. Large scale drug screens have shown that arabinogalactan strains are sensitised to known anti- TB drugs. The work presented in this dissertation aims to shine light on the functionality of the galactan component of arabinogalactan, examining its role in the sensitisation of mycobacteria to known antimycobacterial drugs and its impact on cell envelope characterisation and cell morphology. The CRISPR interference (CRISPRi) genome editing system was used to target genes involved in galactan biosynthesis and generate transcriptional knock down of wecA (also known as rfe, MSMEG_4947) and rfbD (MSMEG_6369) in M. smegmatis, a widely exploited modal for mycobacterial studies. We show that knockdown of both wecA and rfbD did not show hypersensitisation to first-line antibiotics rifampicin, ethambutol, vancomycin or linezolid. In addition, partial transcriptional silencing of wecA altered cell morphology, characterised by significant shortening and widening of cells, however partial transcriptional silencing of rfbD had no significant impact on cell shape. The M. smegmatis CRISPRi strains were finally stained with DMN-Tre, a fluorescent probe that selectively incorporates into the mycolic acid layer of the cell envelope. Morphological analyses revealed altered DMN-Tre signal along the medial axis of the cell, indicating a potential disruption of mycolic acid biosynthesis when galactan biosynthesis is compromised. Notably, loss of polar incorporation of DMN-Tre suggests issues with polar elongation. The findings of this study and its insights support the continuation of research into the role of galactan in maintaining cell envelope integrity and its role in supporting a robust mycolic acid leaflet.